MODERN VIEW ON X-RAY DIAGNOSIS OF CARDIOVASCULAR DISEASES (REVIEW) - A. V. Anikina (Sibirskiĭ nauchnyĭ medit︠s︡inskiĭ zhurnal, 2019)
According to the forecasts of the World Health Organization, cardiovascular diseases will remain the main cause of death of the world population for several decades. Based on this prediction, the diagnosis of heart disease at the preclinical stage remains a major problem for clinicians. For now the main non-invasive imaging methods for cardiovascular damage are still ultrasound and multispiral computed tomography, less often magnetic resonance imaging. In recent years, the application of poorly studied radionuclide methods such as positron emission and single-photon tomography to the diagnosis has been actively discussed. The use of these non-invasive techniques is capable to diagnose the cardiovascular system pathology at earlier terms, but it is necessary to know the possibilities and limitations of each method for the correct analysis and interpretation of the data obtained. In this review, the main aspects of modern radiation and radionuclide cardiologic diagnosis are described. The article is divided into two parts: the first section presents some aspects of individual ray imaging methods; the second included methods of radionuclide diagnostics of the most important diseases of the heart and blood vessels.